The Effects of Learning Motivation towards Student’s Learning Achievement in English (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
English is still regarded as a difficult lesson by most of the students, so studentâ€™s learning achievement in English is low. The Purpose of this research determines The effects of Learning Motivation Towards Studentâ€™s Learning Achievement in English at Kota Tangerang Selatan. The research method used is survey method. Sample size as many as 90 students from SMP Negeri 4 represents International Designed Rating School, SMP Negeri 11 represents National Rating School and SMP Negeri 6 Kota Tangerang Selatan. Data Collection carried out by interview, giving questionnaires and carrying out learning achievement in English test. The research  is conducted in May 2012.Research results show learning motivation variable has significant effects towards studentsâ€™ learning achievement in English. Research results state there is the effects of learning motivation towards studentâ€™s learning achievement in English of class VIII SMP Negeri Kota Tangerang Selatan From the research results, it can be concluded that each increase in learning motivation by one unit will be followed by changing in one unit of student achievement in English as well. Suggestions that can be conveyed are to increase learning motivation, many things can be done, including by giving awards to outstanding students.